Dominant party cohesion in comparative perspective: evidence from South Africa and Namibia. Issue 1 (2nd January 2017) - Cooper, Ian
ABSTRACT: Africa's proliferation of dominant-party regimes is often regarded as an obstacle to democratization. Scholars and practitioners therefore face the task of understanding how and why constitutionally legitimate challenges to dominant party rule occur. This article asks: why do some presidential succession crises act as a catalyst to dominant party fragmentation when others do not? It argues that minority factions are more likely to defect from a dominant party when they have (1) been marginalized by the majority faction and (2) confidence in their mobilizational capacity. Factional purging is in turn traced to autocratic leadership and party under-bureaucratization, whilst high levels of factional self-confidence are linked to crises of dominance and the weakness of extant opposition parties.